2020
DOI: 10.3389/fcell.2020.586487
|View full text |Cite
|
Sign up to set email alerts
|

Roles of TRAFs in Ischemia-Reperfusion Injury

Abstract: Tumor necrosis factor receptor-associated factor (TRAF) proteins are a family of signaling molecules that function downstream of multiple receptor signaling pathways, and they play a pivotal role in the regulation of intracellular biological progresses. These TRAFdependent signaling pathways and physiological functions have been involved in the occurrence and progression of ischemia-reperfusion injury (IRI), which is a common pathophysiological process that occurs in a wide variety of clinical events, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 177 publications
(268 reference statements)
0
1
0
Order By: Relevance
“…Then, when the reperfusion phase begins, the activated endothelial cells produce excessive amounts of ROS, which further cause oxidative stress and inflammatory damage, eventually leading to apoptosis, autophagy, and necrosis ( 19 ). It is currently believed that the mechanism of pulmonary parenchymal I/R injury is similar to that of reperfusion injury in other organs, a process that includes a significant increase in ROS, intracellular calcium influx, endothelial cell injury, complement system activation, and the release of inflammatory mediators such as tumor necrosis factor receptor-related factors ( 20 , 21 ). It has been shown that Nec-1 treatment significantly inhibits IR-induced necrotic cell death and the production of mitochondrial ROS ( 22 ).…”
Section: Mechanisms Of Necroptosis and Lung Diseasesmentioning
confidence: 99%
“…Then, when the reperfusion phase begins, the activated endothelial cells produce excessive amounts of ROS, which further cause oxidative stress and inflammatory damage, eventually leading to apoptosis, autophagy, and necrosis ( 19 ). It is currently believed that the mechanism of pulmonary parenchymal I/R injury is similar to that of reperfusion injury in other organs, a process that includes a significant increase in ROS, intracellular calcium influx, endothelial cell injury, complement system activation, and the release of inflammatory mediators such as tumor necrosis factor receptor-related factors ( 20 , 21 ). It has been shown that Nec-1 treatment significantly inhibits IR-induced necrotic cell death and the production of mitochondrial ROS ( 22 ).…”
Section: Mechanisms Of Necroptosis and Lung Diseasesmentioning
confidence: 99%